2006
DOI: 10.1167/iovs.06-0327
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Retinal Nerve Fiber Layer and Visual Field Sensitivity as Measured by Optical Coherence Tomography in Chiasmal Compression

Abstract: This is the first study to compare the structure-function correlation of RNFL measured by OCT with SAP in patients with chiasmal compression. RNFL is topographically related globally and sectorally to decreased SAP, with the temporal sectors showing the strongest correlations. The correlation between RNFL and VFS strengthens as the time from surgical intervention increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
99
4
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 43 publications
(39 reference statements)
9
99
4
11
Order By: Relevance
“…Our study indicated a significant structure-function correlation when assessed using the linear model evaluated by Pearson's correlation coefficients, especially when VFS loss was expressed in 1/L. These findings are similar to those of previous studies on glaucoma (3,29) and other neuro-ophthalmic conditions (5)(6) , suggesting the existence of a possible linear correlation between visual loss and axonal damage. In our study, although all quadrantic measurements in BA eyes differed significantly from normals, the best structurefunction correlation was found between the superonasal macular thickness and inferotemporal VFS, and not between inferonasal thickness and the superotemporal VFS, the correlation which was smaller than expected.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study indicated a significant structure-function correlation when assessed using the linear model evaluated by Pearson's correlation coefficients, especially when VFS loss was expressed in 1/L. These findings are similar to those of previous studies on glaucoma (3,29) and other neuro-ophthalmic conditions (5)(6) , suggesting the existence of a possible linear correlation between visual loss and axonal damage. In our study, although all quadrantic measurements in BA eyes differed significantly from normals, the best structurefunction correlation was found between the superonasal macular thickness and inferotemporal VFS, and not between inferonasal thickness and the superotemporal VFS, the correlation which was smaller than expected.…”
Section: Discussionsupporting
confidence: 89%
“…A spatial correspondence between retinal ganglion cell (RGC) loss and visual field (VF) defect in patients with glaucoma has been reported by several authors (1)(2)(3)(4) . However, only a few studies evaluated structure-function relationship in optic neuropathies other than glaucoma (5)(6)(7) . Most of them have cor- one with less than 33% fixation losses, false-positive and false negative responses.…”
mentioning
confidence: 99%
“…1,2 Studies evaluating the relationship between functional and structural measurements of the neural structures of the eye are of great importance for diagnosis and monitoring the course of the disease. VF loss, which is usually assessed using standard automated perimetry (SAP), is the most commonly used parameter to estimate the severity of visual loss.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the relationship between these parameters are of great importance not only to provide complementary data on the extent of neural damage in patients at risk of irreversible VF loss, but even more importantly to help estimate the chances of reversing visual loss in conditions such as demyelinating or compressive optic neuropathy. [1][2][3] However, most structurefunction relationship studies have focused on patients with glaucoma, [4][5][6][7] and conclusions have not been directly extrapolatable to other optic pathway conditions. The changes in the structural appearance of the optic nerve head (ONH) and RNFL that accompany the development of VF loss in patients with permanent temporal hemianopia from chiasmal compression represent an important model for assessing the diagnostic performance of different instruments for measuring retinal neural structures.…”
Section: Introductionmentioning
confidence: 99%